Policy Instruments for Water Pollution Control in Developing Countries - Olmstead, Sheila; Zheng, Jiameng (World Bank, Washington, DC, 2019)
This paper surveys the economic theory behind regulatory and other solutions to the stark ambient water pollution problems that exist in many developing countries, and what is known from the empirical economics literature about the effectiveness of these solutions.